SCADA System for Solar MPPT Controller Monitoring. (2016) - Pasc, Petru-Claudiu; Dumitru, Cristian-Dragos
Abstract: The present paper deals with the simulation of a solar photovoltaic MPPT controller used for the supply of a power consumer. The power system contains a photovoltaic generator, MPPT controllers, batteries, power consumers and the connection to a local grid. The solar photovoltaic MPPT controller is implemented by using the "perturb and observe" (P&O) algorithm that varies the PV generator voltage and returns the peak power that can be supply the power consumer. The solar radiation intensity, the power load curve and batteries behavior will also be studied correlated with the solar photovoltaic MPPT controller. The developed application based on the proposed algorithm provides the parameters of the power system components and the power flow. The developed application in CitectSCADA environment simulates the MPPT regulator behavior based on mathematical functions entries for the load curve and for the solar radiation on a given location. The developed application highlights the electrical parameters of all the system components, resulting in an efficient MPPT controller integrated into a solar PV system.